PERANCANGAN APLIKASI PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE JOB ORDER COSTING PADA MEUDANG PERKASA FURNITURE - Mulyanda, Muhammad Irzam; Evayani, Evayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this research is to find out how the system of calculating the cost of goods manufactured that are currently running at Meudang Perkasa Furniture. This company is still calculating the cost of goods manufactured manually, which can lead to errors in the determination of costs incurred to produce goods. In addition, because the process is done manually, the calculation process takes a long time. This study aims to design an application that can help users to know the cost of goods manufactured quickly and precisely. The system designed in this study uses Microsoft Access. This study uses descriptive qualitative method, data collection techniques was done by conducting interviews, observations, and literature studies carried out directly with the owner of the company. This study resulted in a Cost of Goods Manufactured Application that would ease future corporate activities.